Emotional Intelligence and Effective School Management in the Private Schools of Kathmandu Valley - KC, Hari Singh; Rahim, Hazrita Binti Ab.; Kaur, Kamaljeet (Journal of Advanced Academic Research, 2026)
This paper investigated the connection between school management (ESM) and emotional intelligence (EI) of the principals of the private secondary schools in Kathmandu Valley, Nepal. To be more precise, it was to establish whether the two dimensions of EI self-awareness and self-regulation are strongly correlated and forecasting successful school management. The design used was a positivist, quantitative, cross sectional correlational design. Approximately 325 respondents that included principals, vice-principals, coordinators and teachers selected 25 high-performing private schools were used to collect data through a structured questionnaire. Construct validity was determined through the use of exploratory factor analysis, whereas reliability was determined through the use of Cronbach alpha and composite reliability. The data were analyzed with the SPSS version 25 with the application of descriptive statistics, Pearson correlation, and multiple regression analysis. The findings indicated that there was a strong positive relationship between emotional intelligence and successful school management (r ≈ 0.52, p < .001), which confirmed Hypothesis H1. Regression analysis also showed that self-awareness (β= 0.42, p <.001) as well as self-regulation (β= 0.36, p <.001) are significant predictors of effective school management thus supporting the Hypothesis H2. The stronger predictor was self-awareness. The results indicate that emotional intelligence is a vital leadership skill and propose that the effectiveness of school management may be improved by increasing the levels of self-awareness and self-regulation amongst principals, especially in schools with limited resources.